Mechanical Performance of Concrete with Graphene Oxide: Evaluation of Compressive and Splitting Tensile Strength - Montoya, Ismael Eliú Rodas (2025)
Concrete is currently one of the most widely used materials in the world, but its production involves the emission of significant amounts of CO2 due to cement manufacturing. To address this global issue, various materials and methods have been explored. In this context, the incorporation of graphene oxide (GO) into concrete emerges as an innovative solution due to its remarkable physical and chemical properties. GO has been shown to enhance the mechanical properties of concrete, allowing target strength to be achieved with less cement. Therefore, this study aims to evaluate the influence of GO on the mechanical properties and workability of concrete. Four concrete mix designs were evaluated, consisting of a control group and three dosages (0.03%, 0.05%, and 0.08% GO relative to the cement weight). Tests were conducted for compressive strength, split tensile strength, and slump. Results indicate that the 0.08% dosage proved to be optimal, with a 22.71% increase in compressive strength and a 23.37% increase in split tensile strength at 28 days compared to the control mix. However, this dosage exhibited the lowest slump, measuring 139 mm. In conclusion, the incorporation of GO into concrete improves its strength, particularly at early stages, suggesting its potential for structures subjected to heavy loads from the outset.